Chloride Penetration in Lightweight Aggregate Mortars Incorporating Supplementary Cementing Materials - Maria Stratoura; Diana-Ruxandra Iaz; Efstratios Badogiannis (Advances in Civil Engineering)
The current research is aiming to investigate the chlorides’ penetration resistance of 9 different pumice lightweight aggregate mortars (LWAMs). The composition of the mixture is altered by the addition of metakaolin, fly ash, silica fume, and ground granulated blast furnace slag, substituting 10% and 20% of cement by mass. Workability and compressive strength of the mortars are studied together with durability parameters like water absorption due to capillary absorption and porosity. Moreover, the mortar resistance to chloride penetration is evaluated through non-steady-state chloride migration coefficient, complying to NT BUILD 492 standard. Summarizing all the laboratory test results, while the addition of metakaolin in the range of 20% led to better workability, higher compressive strength, lower sorptivity, and lower volume of open porosity, it did not improve the resistance against chlorides’ penetration.